PERANCANGAN SISTEM INFORMASI PELAYANAN JASA LAUNDRY NEW AND CARE BERBASIS WEB - Romandhon Akbar Setiadi, (2020)
New and Care is a laundry business that focus on washing shoes, bags and hats. Problem that existed in New and Care laundry service system is administrative process that have yet to be computerized. Begins with customer data that is still documented and kept in the customer records, also the laundry receipt transaction is still recorded in the laundry receipt confirmation. And the payment cannot be counted and stored using computerized systems. It takes a very long time to count, also there's a lot of mistakes that happen. Therefore, it needs web-based system design to improve laundry service, and helps produce more accurate and delicate import reports and transaction reports, thereby reducing the occurrence of errors. The design of the New and Care laundry service information system was built using the Waterfall design method which has several stages, namely requirements analysis, design, coding, testing and ready to be implemented. For system analysis using the PIECES analysis method in order to find the main problems contained in the system. Data collection techniques with observation, study of literature, and interviews. This research has resulted in a web-based Laundry New And Care Services Information System, so that it has facilitated services in New and Care Laundry.